Pendampingan Organisasi Kader Kesehatan Desa Dalam Manajemen Program Posyandu - Ryan Agus Faisal; Rani Darma Sakti Tanjung (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2024)
The Village health cadres play a vital role in the success of the Posyandu (Integrated Health Service Post) program as the frontline of community-based health services. However, challenges such as limited managerial capacity, insufficient resource support, and lack of continuous mentoring often hinder the effectiveness of the program’s implementation. This article aims to describe the process and outcomes of mentoring village health cadre organizations in improving their program management skills at the Posyandu. The research employs a qualitative approach using content analysis from activity reports, interviews, and field documentation. The results show that structured, participatory, and continuous mentoring significantly enhances cadres’ skills in planning, implementing, and evaluating Posyandu activities. Moreover, mentoring improves cadres’ motivation and sense of responsibility toward program sustainability. Support from village governments, local health centers (puskesmas), and communities plays a crucial role in maintaining the effectiveness of mentoring. Therefore, a collaborative mentoring model is an effective strategy to strengthen the capacity of village health cadres in managing Posyandu programs at the village level.